Perancangan sistem informasi strategik pada ukm xyz untuk memaksimalkan pemasaran dan efisiensi biaya - Elizabeth, Elizabeth; Arifin, Agus Zainul (Jurnal Manajemen, 2017)
The goal of writing this research is to Maximize Marketing Through E-Commerce Small Mediun Enterprise (SME) XYZ. The structure of composing this research is refers of methodology IT Strategic Planning which created by John Ward and Peppard in the book The Strategic Management of Information Systems (2016). The analysis start with company’s condition using internal analysis tools such as SWOT and external analysis tools such as PEST and Porter Analysis, Internal Environment IS/IT, External Environment IS/IT. The result of the analysis are then processed and later generate initiatives in form of IS Business Strategies, IS/IT Management Strategies, and IT Strategies. From that analysis result can take a summary and recommend for IS Business Strategy are create Website E-Commerce with Cloud Computing Cozy and integrated with BI (Business Intelligence) Google Analytics, Install SMS Gateway Gammu, and optimalize online marketing with social media. For IS/IT management strategy are analysis cost and benefit from this project. IT Strategy analysis are recommend software and IT Roadmap.